Highly cross-linked polyethylene still outperforms conventional polyethylene in THA: 10-year RSA results - Bergvinsson , Halldor; Zampelis, Vasilis; Sundberg, Martin; Flivik, Gunnar (Acta Orthopaedica, 2021)
Background and purpose — Cup wear in total hip arthroplasty (THA) can be affected by different manufactur- ing processes of the polyethylene (PE). We report the long- term wear pattern differences, as well as early creep behav- ior, between conventional PE and highly cross-linked PE (HXLPE) liners, as measured with radiostereometry (RSA) up to 10 years. We also compare migration and clinical out- come of 2 similar uncemented cups with different backside surface roughness. Patients and methods — We included 45 patients with primary osteoarthritis. 23 received a conventional liner and 22 an HXLPE liner in a similar uncemented cup, but with a slightly rougher surface. The patients were followed up with RSA and hip-specific outcome questionnaire (HOOS) at 3 months, 1, 2, 5, and 10 years. Results — During the first 3 months both liners showed expected deformation with mean proximal head penetra- tion of 0.39 mm (conventional PE) and 0.21 mm (HXLPE). Between 3 months and 10 years there was a difference in annual wear with 0.12 mm/year for the conventional liner and 0.02 mm/year for the HXLPE liner. The cup with rougher surface had less initial migration but both types had stabilized after 3 months. The HOOS scores improved after surgery and remained high for both groups throughout the study period. Interpretation — Up to 10 years the HXLPE has con- sistent lower annual wear, possibly contributing to longer survival of the THA, compared with conventional PE. All patients reported good results regardless of liner type.